Catalyst for epoxidation reactions and preparation thereof
Amorphous titanium-doped silica catalyst containing pentahedral coordinated titanium substances was prepared by sol-gel synthesis method, which solved the problem of lack of high-active catalysts in the prior art and achieved efficient production of propylene oxide.
Patent Information
- Application Number
- CN202380065519.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-12
- Filing Date
- 2023-08-29
- Publication Date
- 2025-04-25
AI Technical Summary
The manufacturing method of amorphous silica materials containing pentahedral coordination titanium substances is lacking in the prior art.
An amorphous titanium-doped silica catalyst containing pentahedral coordinated titanium substances is prepared by a sol-gel synthesis method, including forming a catalyst hydrogel precursor, drying, calcining and hydrophobizing treatment.
High activity and selective conversion of propylene into propylene oxide is achieved, suitable for large-scale industrial production, and improves the stability and performance of the catalyst.
Smart Images

Figure BDA0005307930700000011 
Figure BDA0005307930700000101 
Figure BDA0005307930700000171
Abstract
Description
Technical Field
[0001] The present invention relates to a process for preparing propylene oxide comprising the reaction of propylene with ethylbenzene hydroperoxide in the presence of a catalyst, as well as to catalysts employed in such a process and to a process for their manufacture. Background Art
[0002] The process for epoxidizing an olefin to an ethylene oxide product generally involves the reaction of an olefin with an organic hydroperoxide in the presence of a heterogeneous catalyst. A commonly known process for making propylene oxide involves the co-production of propylene oxide and styrene monomers starting from ethylbenzene, a process sometimes referred to as a propylene oxide / styrene monomer (PO / SM) process. Generally, the process involves the following steps:
[0003] (i) reacting ethylbenzene (EB) with oxygen to form ethylbenzene hydroperoxide (EBHP),
[0004] (ii) reacting the ethylbenzene hydroperoxide (EBHP) thus obtained with propylene in the presence of an epoxidation catalyst to produce propylene oxide (PO) and 1-phenylethanol (methylphenylcarbinol, MPC), and
[0005] (iii) Dehydration of 1-phenylethanol (MPC) to styrene (SM) using a suitable dehydration catalyst.
[0006]
[0007] Many titanium-containing siliceous materials have been disclosed in the prior art as catalysts for the central epoxidation step. More specifically, it has been disclosed in the prior art that crystalline zeolite materials containing a pentahedrally coordinated titanium species show catalytic activity in epoxidation reactions (Zuo Y et al., RSC Adv., 2015, 5, 17897, Role of pentahedrally coordinated titanium in titanium silicalite-1 in propene epoxidation). On the other hand, amorphous silica materials containing a pentahedrally coordinated titanium species have not been suggested as catalysts for this purpose. In fact, amorphous silica materials containing a pentahedrally coordinated titanium species have not been disclosed in the prior art at all, because it is not known how to make such materials to date.
[0008] Prior art methods for obtaining titanium-doped amorphous silica include vapor deposition of titanium species on dry silica (EP1572362A1); titanium doping of dry amorphous silica materials in anhydrous organic solvents (US5932751); titanium doping of amorphous silica by contacting dry amorphous silica materials with a solution of titanium tetrachloride, nitric acid and concentrated hydrogen peroxide (US4367342A); titanium doping of amorphous silica by contacting dry amorphous silica materials with a solution of titanyl sulfate (US2015182959A1); and titanium-doped silica generated from an organic precursor of titanium and silica (US2018147560A1). However, none of these methods produces amorphous silica with a pentahedrally coordinated titanium species. Summary of the invention
[0009] The present invention is based on the discovery of amorphous silica materials comprising pentahedrally coordinated titanium species and robust methods for their manufacture, and further based on the discovery that such materials exhibit significant catalytic activity for the conversion of propylene to propylene oxide.
[0010] In a process for converting propylene into propylene oxide in a propylene oxide / styrene monomer (PO / SM) process, the catalyst based on amorphous titanium-doped silica containing a pentahedrally coordinated titanium species of the present invention exhibits high activity and selectivity for the target product, and the catalyst preparation method of the present invention can be adapted to large-scale industrial production.
[0011] The method of the present invention is intended to produce a catalyst comprising amorphous titanium-doped silica, the amorphous titanium-doped silica comprising pentahedrally coordinated titanium species, the method comprising the following steps:
[0012] a. a sol-gel synthesis of a catalyst hydrogel precursor, the sol-gel synthesis comprising the following steps:
[0013] i. adding water glass exhibiting a viscosity in the range of 400 to 600 mPa*s to the acid, thereby producing a silica gel exhibiting a residual water content Xwa in the range of Xw1 to Xw2,
[0014] ii. removing impurities from the silica gel by washing the silica gel with an acidic aqueous solution, thereby producing purified silica gel,
[0015] iii. Forming a catalyst hydrogel precursor via alternative a:
[0016] doping the purified silica gel by contacting the purified silica gel with an acidic aqueous solution of a titanium salt, thereby producing titanium-doped silica gel, and
[0017] aging the titanium-doped silica gel by suspending it in an aging solution at a temperature in the range of 60° C. to 90° C. for a time span in the range of 4 h to 6 h, wherein the liquid portion of the suspension thus formed exhibits a pH value in the range of 5.5 to 7.5, thereby producing a catalyst hydrogel precursor exhibiting a titanium content Xt in the range of Xt1 to Xt2,
[0018] or
[0019] The catalyst hydrogel precursor is formed via alternative b as follows:
[0020] Aging the purified silica gel by suspending the purified silica gel in an aging solution at a temperature in the range of 60° C. to 90° C. for a time span in the range of 4 h to 6 h, wherein the liquid portion of the suspension thus formed exhibits a pH value in the range of 5.5 to 7.5, thereby producing an aged purified silica gel, and
[0021] doping the aged purified silica gel by contacting the aged purified silica gel with an acidic aqueous solution of a titanium salt, thereby producing a catalyst hydrogel precursor exhibiting a titanium content Xt in the range of Xt1 to Xt2,
[0022] b. drying the catalyst hydrogel precursor until the residual water content Xwb of the dried catalyst hydrogel precursor is in the range of Xw3 to Xw4,
[0023] c. calcining the dried catalyst hydrogel precursor,
[0024] in,
[0025] Xw1=40wt%, Xw2=60wt%,
[0026] Xt1=0.85wt%, Xt2=1.9wt%,
[0027] Xw3=1wt%, Xw4=7wt%,
[0028] And among them,
[0029] The residual water content Xwa and Xwb of the sample is determined as the weight loss exhibited by a 100 g aliquot after drying at 200° C. for four hours in a drying oven under atmospheric conditions,
[0030] And among them,
[0031] The titanium content Xt of the sample was determined by elemental analysis via optical emission spectroscopy with inductively coupled plasma (ICP-OES) after: dissolving the sample by adding 5 ml of ultrapure water, 1.5 ml of a 0.2 wt % D-mannitol aqueous solution and 5 ml of a 40 wt % to 50 wt % HF aqueous solution to 1 g of the sample; subsequently removing the liquid component by heating to 120° C.; and successively, dissolving the remaining residue in 1 ml of a 65 wt % to 70 wt % HNO 3 aqueous solution and 2 ml of H 2 O 2 under heat treatment at 120° C. for 1 h; and diluting the resulting liquid 10 times with ultrapure water before measurement,
[0032] And among them,
[0033] The Ti content of the solid material is calculated on a dry mass basis and corresponds to the content of elemental titanium. DETAILED DESCRIPTION
[0034] The method for making the catalyst of the present invention starts with the sol-gel synthesis of the catalyst hydrogel precursor. It is important to understand the differences between various types of silica gel in this context. In the context of this application, the following definitions will be followed:
[0035] (1) Silica hydrogel is a material made by mixing sulfuric acid with sodium (or potassium) water glass in an aqueous system via a sol-gel process. The water content of such hydrogels depends on the ratio of sulfuric acid to water glass and is generally in the range of 20 to 80 wt%.
[0036] (2) Silica xerogel is a material produced by drying the silica hydrogel according to definition (1) to a water content of less than 20 wt%.
[0037] (3) Type I metal-silica-cogel hydrogel is a material made by mixing sulfuric acid, a metal salt solution and sodium (or potassium) water glass in an aqueous system via a sol-gel process. The water content of such type I metal-silica-cogel hydrogel depends on the ratio of the sulfuric acid, the metal salt and the water glass, and is generally in the range of 20 to 80 wt%. Generally, metal sulfates are used as metal salts.
[0038] (4) Type I metal-silica-cogel xerogel is a material produced by drying the type I metal-silica-cogel hydrogel according to definition (3) to a water content of less than 20 wt %.
[0039] (5) Type II metal-silica-cogel hydrogel is a material produced by a sol-gel process in which a silica hydrogel according to definition (1) is first obtained. After gelation of the silica hydrogel, an aqueous solution of a metal salt is used to impregnate the silica hydrogel (before a drying step). Wherein "impregnation" means adding a liquid solution of a metal salt to a non-liquid substance in order to deposit the metal onto the substance. The water content of such a Type II metal-silica-cogel hydrogel is generally in the range of 20 to 80 wt%.
[0040] (6) The type II metal-silica-cogel xerogel is a material produced by drying the type II metal-silica-cogel hydrogel according to definition (5) to a water content of less than 20 wt %.
[0041] (7) Type III metal-silica-cogel xerogel is a material according to definition (2) made via a sol-gel process. After preparing the silica xerogel, a metal salt solution is used to impregnate the silica xerogel (after a drying step). Wherein "impregnation" means adding a liquid solution of a metal salt to a non-liquid substance in order to deposit the metal onto the substance. Typically, the impregnated material is dried after impregnation to remove the remaining impregnation solution. The impregnation solution can be water-based or non-aqueous-based. The water content of such Type III metal-silica-cogel xerogel is less than 20 wt%.
[0042] The catalyst of the present invention is based on a Type II metal-silica-cogel hydrogel according to definition (5) obtained after step (a)(iii) of the method, wherein titanium is used as a metal dopant (using an aqueous solution of titanyl sulfate to impregnate the silica hydrogel); and a Type II metal-silica-cogel xerogel according to definition (6) obtained after step (b) of the method.
[0043] In the first step of the method for making the catalyst of the present invention, water glass is added to the acid in a sintered flow reactor to obtain silica gel. The corresponding method for obtaining silica gel is well known in the art (see, for example, The colloid chemistry of silica and silicates, Ralph K. Iler, Cornell University Press, Ithaca, New York, 1955). Suitable acid for the method is dilute sulfuric acid at a concentration of 5 to 50wt%, but other acids can be selected by those skilled in the art. The water glass used in this step needs to show a viscosity in the range of 400 to 600mPa*s. After contacting the acid, the water glass drops immediately sink to the bottom of the reactor to form a bed of silica gel particles. In order to obtain a material comprising titanium-doped amorphous silica, the titanium-doped amorphous silica comprises a pentahedra-coordinated titanium substance according to the present invention, and the residual water content Xwa of these silica gel particles needs to be in the range of 40 to 60wt%.
[0044] In this context it is important to note that the water content of the silica gel particles obtained at this stage of the process (i.e. at the end of step (a)(i)) does not undergo significant changes until the end of step (a)(iii) of the process. Thus, the water content of the silica gel particles obtained at this stage of the process (i.e. at the end of step (a)(i)) is substantially the same as the water content of the catalyst hydrogel precursor material obtained at the end of step (a)(iii). It is therefore not important whether the residual water content is determined at the end of step (a)(i) of the process or at the end of step (a)(iii) in order to determine whether Xwa is within the range of Xw1 to Xw2.
[0045] The viscosity of the water glass used in this step is a key determinant of the residual water content of the obtained silica gel particles. Increasing the viscosity of the water glass used in this stage will reduce the residual water content of the obtained silica gel particles, and vice versa. Therefore, it is necessary to use a water glass showing a viscosity in the range of 400 to 600 mPa*s in this step.
[0046] The residual water content of the material obtained is determined as the weight loss exhibited by a 100 g aliquot after drying at 200° C. in a drying cabinet under atmospheric conditions for four hours.
[0047] In the next step, impurities are removed from the silica gel by circulating an acidic aqueous solution through the bed of gel particles. Typically, this process is carried out for about 2 hours, while the acidic aqueous solution is recycled by continuously pumping it through an ion exchange column (typically styrene-divinylbenzene functionalized with aminophosphonic acid) to remove metal cations. The washing step can be repeated with fresh acidic aqueous solution at elevated temperature (typically about 50 to 70° C.) to remove additional impurities until the following stoichiometric purity levels are obtained: total metal content <1%, Sb≤0.1ppm, Sn≤0.1ppm, Zn≤0.0ppm, Zr≤0.2ppm, Al≤0.8ppm, As<0.01ppm, B<0.01ppm, Ba≤2.2ppm, Ca≤0.3ppm, Cr≤0.1ppm, Cu≤0.0ppm, Fe≤2.9ppm, K≤0.1ppm, Mg≤0.0ppm, Na≤1.5ppm, Ni<0.01ppm. Finally, the acid is drained from the reactor and the gel particles are rinsed with deionized water, typically for about 1 h.
[0048] In a subsequent step, a catalyst hydrogel precursor is formed from the purified silica gel obtained in the previous step. The following two alternatives can be implemented in order to achieve this:
[0049] In alternative a, the purified silica gel is first doped by contacting it with an acidic aqueous solution of a titanium salt, thereby producing titanium-doped silica gel, and then the titanium-doped silica gel is aged by suspending it in an aging solution at a temperature in the range of 60°C to 90°C for a time span in the range of 4h to 6h, wherein the liquid portion of the suspension thus formed exhibits a pH value in the range of 5.5 to 7.5, thereby producing a catalyst hydrogel precursor exhibiting a titanium content Xt in the range of Xt1 to Xt2.
[0050] In alternative b, the purified silica gel is aged by suspending it in an aging solution at a temperature in the range of 60°C to 90°C for a time span in the range of 4h to 6h, wherein the liquid portion of the suspension thus formed exhibits a pH value in the range of 5.5 to 7.5, thereby producing an aged purified silica gel, and then the aged purified silica gel is doped by contacting it with an acidic aqueous solution of a titanium salt, thereby producing a catalyst hydrogel precursor exhibiting a titanium content Xt in the range of Xt1 to Xt2.
[0051] For the purpose of doping with titanium, a doping solution of a titanium salt in dilute acid, typically titanyl sulfate (TiO(SO4)) in a concentration ranging from 2 to 10 wt% in sulfuric acid at a concentration of about 20 to 25 wt%, is contacted with the purified silica gel or with the aged purified silica gel in the reactor, typically for about 1 h. The titanium concentration in the doped product can be increased by increasing the titanium concentration in the doping solution, by increasing the amount of doping solution in contact with the silica gel, and by increasing the duration of contact between the doping solution and the silica gel. Likewise, reducing the respective physical quantities reduces the titanium concentration in the doped product. The titanium-doped silica gel is then washed with deionized water.
[0052] For the purpose of aging, the purified silica gel or the titanium-doped silica gel is suspended in an aging solution at a temperature in the range of 60°C to 90°C for a time span in the range of 4h to 6h, followed by washing with deionized water. The aging solution needs to impart a pH value in the range of 5.5 to 7.5 to the liquid part of the suspension formed. Furthermore, the aging solution needs to consist exclusively of components that can be completely removed by heating to about 300°C. Dilute ammonium acetate solutions (1 to 50 wt%) exhibiting a pH value in the range of 5.5 to 6.5 are typical examples of such aging solutions. For the liquid part of the suspension, it is important to adhere to a pH range of 5.5 to 7.5, since aging significantly affects the textural properties of the silica matrix, i.e. the BET specific surface area A S,BET , average pore width D P,BJH and the pore volume V P,总 , as described in academic literature (e.g., The influence of pH on the surface characteristics of silica gelsoaked in aqueous solutions, D. Dollimore, G. M. Heal, Journal of Applied Chemistry, 1962, 12, 445-450; The colloid chemistry of silica and silicates, Ralph K. Iler, Cornell University Press, Ithaca, New York, 1955). pH values below the required range will result in a higher BET specific surface area A S,BET , lower average pore width D P,BJH and a slightly lower pore volume V P,总 , while pH values above the desired range will result in a lower BET surface area A S,BET, higher average pore width D P,BJH and a slightly higher pore volume V P,总 At a constant pH value (within the desired range), an increase in temperature results in a BET surface area A S,BET The decrease in the average pore width D P,BJH The increase of pore volume V P,总 The BET specific surface area A S,BET The increase of the average pore width D P,BJH The decrease in pore volume V P,总 The structural properties are selected so as to provide a molecule of a size suitable for being selectively converted into the desired product in the catalytic reaction.
[0053] Finally, the water is rinsed off and a catalyst hydrogel precursor showing a residual water content of 40 to 60 wt% and a titanium content of 0.85 to 1.9 wt% is obtained. The titanium content of the sample is determined by elemental analysis via optical emission spectroscopy (ICP-OES) with inductively coupled plasma after the following dissolution: 5 ml of ultrapure water, 1.5 ml of D-mannitol solution (1 g of D-mannitol in 499 g of ultrapure water) and 5 ml of HF (40 to 50 wt% aqueous solution) are added to 1 g of the sample. Then, the resulting solution is heated to 120° C. to remove the liquid. The remaining residue is successively dissolved in 1 ml of HNO3 (65 to 70 wt% aqueous solution) and 2 ml of H2O2 under a heat treatment at 120° C. for 1 h. The resulting liquid is diluted to 1 / 10 with ultrapure water before measurement.
[0054] The Ti content of the solid material mentioned in the present invention is / has been calculated on a dry mass basis. The residual water content of the obtained material is determined as the weight loss exhibited by a 100 g aliquot after drying at 200° C. in a drying cabinet under atmospheric conditions for four hours.
[0055] Subsequently, the catalyst hydrogel precursor is dried (typically at a temperature of 150 to 170° C., at a heating rate of about 2 to 5° C. / minute) to a residual water content in the range of 1 to 7 wt %, producing a dried catalyst hydrogel precursor. Drying can be carried out, for example, in a drying oven under atmospheric conditions. Residual water is determined as the weight loss exhibited by a 100 g aliquot after drying at 200° C. in a drying oven under atmospheric conditions for four hours.
[0056] The dried catalyst hydrogel precursor is then calcined (typically at a temperature of about 800°C) to produce a calcined catalyst hydrogel precursor. Calcination can be performed in a furnace under atmospheric conditions.
[0057] In a preferred embodiment of the present invention, the calcined catalyst hydrogel precursor is further hydrophobized with a hydrophobic agent in liquid phase (the hydrophobic agent is a tri-substituted or tetra-substituted organosilane, such as dimethyltrimethylsilylamine, bis(dimethylamino)diethylsilane, hexamethyldisilazane). For this purpose, the hydrophobic agent is dissolved in a solvent (usually a high boiling point solvent, such as an aromatic high boiling point solvent) and contacted with the calcined catalyst hydrogel precursor under stirring. Then, the solid material is filtered out and dried to produce a catalyst.
[0058] The titanium content of all solid materials mentioned in the context of the present invention is determined by elemental analysis via optical emission spectroscopy (ICP-OES) with inductively coupled plasma. Before measurement, the sample is completely dissolved as follows: 5ml of ultrapure water, 1.5ml of D-mannitol solution (1g of D-mannitol in 499g of ultrapure water) and 5ml of HF (40 to 50wt% aqueous solution) are added to 1g of the sample. Then, the resulting solution is heated to 120°C to remove the liquid. The remaining residue is successively dissolved in 1ml of HNO3 (65 to 70wt% aqueous solution) and 2ml of H2O2 under a heat treatment of 120°C for 1h. The resulting liquid is diluted to 1 / 10 with ultrapure water before measurement.
[0059] The titanium content of all solid materials mentioned in the context of the present invention is / has been calculated on a dry mass basis. The titanium content of all solid materials mentioned corresponds to the content of elemental titanium. The difference between the titanium content correspondingly obtained for a sample of catalyst hydrogel precursor (i.e. the material obtained after step (a) (iii) of the process of the present invention) and the titanium content obtained for a sample of the same material batch that has additionally undergone any or all subsequent steps of the process of the present invention (i.e. steps b, c, d) is negligible, i.e. less than one percent of the value obtained.
[0060] As for the BET specific surface area A of the catalyst S,BET , average pore width D P,BJH and the pore volume V P,总 , characterized the catalyst. BET specific surface area A S,BET , average pore width D P,BJH and the pore volume V P,总It can be derived from the nitrogen physical adsorption isotherm, as measured, for example, on a Micromeritics ASAP2420 analyzer at 77 K. Before the measurement, each sample must be degassed for 10 h at 300 ° C. in a vacuum of 40 to 50 mbar for the calcined material, and for the hydrophobized material, each sample must be degassed for 10 h at 110 ° C. in a vacuum of 40 to 50 mbar. The Brunnauer-Emmett-Teller (BET) method according to DIN 9277:2014 is used to calculate the specific surface area A S,BET . Average pore width D P,BJH and the total pore volume V P,总 is calculated by applying the method of Barrett, Joyner and Halenda (BJH) using the desorption branch of the isotherm (see Journal of the American Chemical Society, 73: 373-380, 1951).
[0061] Pentahedrally coordinated titanium species can be detected in the silica matrix by their specific spectral signature, namely
[0062] a. DR-UV / Vis band maximum between 220 and 245 nm,
[0063] b. at least 75% of the DR-UV / Vis derived intensity fraction below 275 nm (SIb275),
[0064] Wherein SIb275 is determined by measuring the diffuse reflectance (DR)-UV / Vis of the material, wherein the measured reflectivity is converted into Kubelka-Munk units, and the integrated intensity measured between 200 and 275 nm (Ai, 275 nm) is divided by the integrated intensity measured between 200 and 375 nm (Ai, total) according to the following formula: SIb275 = (Ai, 275 nm) / (Ai, total).
[0065] Therefore, as for their intensity share below 275 nm (defined herein as SI b275) and the position of the spectral band maximum (the highest point of the curve), the obtained material is characterized by diffuse reflectance (DR)-UV / Vis, wherein the measured reflectivity is converted into Kubelka-Munk units (see Reflectance Spectroscopy, W. WM. Wendlandt, HG Hecht, Interscience Publishers / John Wiley NY, 1966; Reflectance Spectroscopy G. Kortüm, Springer Berlin, 1969; Interpreting Diffuse Reflectance and Transmittance: A Theoretical Introduction to Absorption Spectroscopy of Scattering Materials, DJ Dahm, KD Dahm, IM Publications Open LLP Chichester, 2007). The intensity component below 275 nm is obtained according to equation 1 by converting the integrated intensity between 200 and 275 nm (A i,275nm ) divided by the integrated intensity of the entire band between 200 and 375 nm (A i,总 ) is used to calculate. Band integration is performed in the same way as chromatographic peak integration to obtain integrated intensity (see Gas Chromatography, IAFolis, Wiley & Sons Ltd, 1995).
[0066]
[0067] In one aspect, the present invention is directed to a catalyst for converting propylene to propylene oxide in a propylene oxide / styrene monomer process, the catalyst comprising titanium-doped amorphous silica comprising a pentahedrally coordinated titanium species.
[0068] Furthermore, the present invention relates to a catalyst obtainable by the catalyst production process of the present invention.
[0069] During the research of the present invention, it was found that catalysts exhibiting a titanium content within a specific range can obtain particularly beneficial catalytic properties. Therefore, in a preferred embodiment of the present invention, Xt is selected in the range of Xt1=1wt% to Xt2=1.9wt%. In a particularly preferred embodiment of the present invention, Xt is selected in the range of Xt1=1.4wt% to Xt2=1.8wt%. In another particularly preferred embodiment of the present invention, Xt is selected in the range of Xt1=1.6wt% to Xt2=1.8wt%.
[0070] Furthermore, in the context of the present invention, it was found that a catalyst having particularly beneficial catalytic properties can be obtained when the catalyst hydrogel precursor exhibits a residual water content Xwa within a specific range. Therefore, in a preferred embodiment of the present invention, the catalyst hydrogel precursor exhibits a residual water content Xwa within the range of Xw1=45wt% to Xw2=60wt%. In another preferred embodiment of the present invention, the Xwa of the catalyst hydrogel precursor is selected within the range of Xw1=47wt% to Xw2=60wt%. In a particularly preferred embodiment of the present invention, the Xwa of the catalyst hydrogel precursor is selected within the range of Xw1=52wt% to Xw2=57wt%.
[0071] A preferred embodiment of the present invention relates to a catalyst for converting propylene to propylene oxide in a propylene oxide / styrene monomer process, said catalyst exhibiting a DR-UV / Vis derived intensity fraction below 275 nm (SI b275 ), and a DR-UV / Vis band maximum between 220 and 245 nm. In a more preferred embodiment, the present invention relates to a catalyst for converting propylene to propylene oxide in a propylene oxide / styrene monomer process, said catalyst exhibiting a DR-UV / Vis derived intensity fraction below 275 nm (SI b275 ), and the DR-UV / Vis band maximum between 220 and 245 nm.
[0072] In the context of the present invention, the structural parameters of the catalyst according to the present invention, such as the BET specific surface area A S,BET , average pore width D P,BJH and the pore volume V P,总 Can be tailored to the requirements for converting propylene to propylene oxide in a propylene oxide / styrene monomer process. It has been found that, in practice, selection of these parameters within certain ranges results in particularly effective catalysts.
[0073] Thus, in a preferred embodiment, the present invention is directed to a catalyst for converting propylene to propylene oxide in a propylene oxide / styrene monomer process, said catalyst exhibiting a 350 to 650 m / s ratio. 2 The BET specific surface area A in the range of S,BET In a more preferred embodiment, the present invention is directed to a catalyst for converting propylene to propylene oxide in a propylene oxide / styrene monomer process, said catalyst exhibiting a 400 to 550 m 2 The BET specific surface area A in the range of s,BET .
[0074] Additionally, in a preferred embodiment, the present invention relates to a catalyst for converting propylene to propylene oxide in a propylene oxide / styrene monomer process, said catalyst exhibiting an average pore width D in the range of 4 to 8 nm. P,BJH In a more preferred embodiment, the present invention relates to a catalyst for converting propylene to propylene oxide in a propylene oxide / styrene monomer process, said catalyst exhibiting an average pore width D in the range of 4 to 5 nm. P,BJH ,
[0075] The average pore width D P,BJH is derived from the nitrogen physisorption isotherms, as measured on a Micromeritics ASAP 2420 analyzer at 77 K, wherein prior to the measurement each sample was degassed at 300 °C for 10 h in a vacuum of 40 to 50 mbar for the calcined material and at 110 °C for 10 h in a vacuum of 40 to 50 mbar for the hydrophobized material, and the average pore width D P,BJH is calculated by applying the method of Barrett, Joyner and Halenda (BJH) using the desorption branch of the isotherm as described in Journal of the American Chemical Society, 73:373-380, 1951.
[0076] Additionally, in a preferred embodiment, the present invention relates to a catalyst for converting propylene to propylene oxide in a propylene oxide / styrene monomer process, said catalyst exhibiting a 0.4 to 1.0 cm 3 The pore volume V in the range of P,总 In a more preferred embodiment, the present invention is directed to a catalyst for converting propylene to propylene oxide in a propylene oxide / styrene monomer process, said catalyst exhibiting a 0.7 to 0.9 cm 3 The pore volume V in the range of P,总 ,
[0077] The pore volume V P,总 is derived from the nitrogen physisorption isotherms, as measured on a Micromeritics ASAP2420 analyzer at 77 K, wherein prior to the measurement each sample was degassed at 300 °C for 10 h in a vacuum of 40 to 50 mbar for the calcined material and at 110 °C for 10 h in a vacuum of 40 to 50 mbar for the hydrophobized material, and the pore volume V P,总 is calculated by applying the method of Barrett, Joyner and Halenda (BJH) using the desorption branch of the isotherm as described in Journal of the American Chemical Society, 73:373-380, 1951.
[0078] In a particularly preferred embodiment, the present invention is directed to a catalyst for converting propylene to propylene oxide in a propylene oxide / styrene monomer process, said catalyst exhibiting the following:
[0079] a. Titanium content in the range between 1.6 and 1.8 wt%,
[0080] b.400 to 450m 2 BET specific surface area A between / g s,BET ,
[0081] c. Average pore width D between 4.5 and 5 nm P,BJH ,
[0082] d.0.7 to 0.8 cm 3 The pore volume V between P,总
[0083] The titanium content Xt of the sample was determined by elemental analysis via optical emission spectroscopy with inductively coupled plasma (ICP-OES) after: dissolving the sample by adding 5 ml of ultrapure water, 1.5 ml of a 0.2 wt % D-mannitol aqueous solution and 5 ml of a 40 wt % to 50 wt % HF aqueous solution to 1 g of the sample; subsequently removing the liquid component by heating to 120° C.; and successively, dissolving the remaining residue in 1 ml of a 65 wt % to 70 wt % HNO 3 aqueous solution and 2 ml of H 2 O 2 under heat treatment at 120° C. for 1 h; and diluting the resulting liquid 10 times with ultrapure water before measurement,
[0084] And among them,
[0085] The Ti content of solid materials is calculated on a dry mass basis and corresponds to the content of elemental titanium,
[0086] The average pore width D P,BJH is derived from the nitrogen physisorption isotherms, as measured on a Micromeritics ASAP 2420 analyzer at 77 K, wherein prior to the measurement each sample was degassed at 300 °C for 10 h in a vacuum of 40 to 50 mbar for the calcined material and at 110 °C for 10 h in a vacuum of 40 to 50 mbar for the hydrophobized material, and the average pore width D P,BJH is calculated by applying the method of Barrett, Joyner and Halenda (BJH) using the desorption branch of the isotherm, as described in Journal of the American Chemical Society, 73:373–380, 1951,
[0087] The pore volume V P,总 is derived from nitrogen physisorption isotherms, as measured on a Micromeritics ASAP2420 analyzer at 77 K, where before measurement each sample was degassed in vacuum at 300 °C for 10 h for the calcined material and at 110 °C for 10 h for the hydrophobized material, and the pore volume V P,总 is calculated by applying the method of Barrett, Joyner and Halenda (BJH) using the desorption branch of the isotherm as described in Journal of the American Chemical Society, 73:373-380, 1951.
[0088] Another aspect of the present invention relates to an oxidation reaction carried out in the presence of a catalyst according to the present invention. More specifically, the present invention relates to a process for the preparation of propylene oxide comprising the reaction of propylene with ethylbenzene hydroperoxide in the presence of a catalyst according to the present invention. In particular, the present invention relates to a process for the preparation of propylene oxide comprising the reaction of propylene with ethylbenzene hydroperoxide in the presence of a catalyst obtainable by the catalyst manufacturing process of the present invention.
[0089] The catalyst of the present invention is used in oxidation reactions, and can be particularly used to catalyze the epoxidation of olefins with organic hydroperoxides. The epoxidation process of olefins is well known in the art.
[0090] In a particularly preferred embodiment, the catalyst obtained according to the process of the present invention is used in the co-production of propylene oxide and styrene starting from ethylbenzene. Generally, such a process involves the following steps: reacting ethylbenzene (EB) with oxygen or air to form ethylbenzene hydroperoxide (EBHP); reacting the ethylbenzene hydroperoxide (EBHP) thus obtained with propylene in the presence of an epoxidation catalyst to produce propylene oxide (PO) and 1-phenylethanol (methylphenylcarbinol, MPC); and dehydrating the 1-phenylethanol (MPC) to styrene (SM) using a suitable dehydration catalyst.
[0091] In the epoxidation reaction, the molar ratio of olefin to hydroperoxide can vary widely, and a molar excess of either olefin or hydroperoxide of up to 100: 1 can be used. Preferably, a molar ratio of olefin to hydroperoxide varying from about 50: 1 to about 1: 10 is satisfactory, although a molar ratio of olefin to hydroperoxide of about 20: 1 to about 1: 1 is particularly preferred.
[0092] Organic hydroperoxides are prepared by direct oxidation methods, which are well known in the art. For example, molecular oxygen can be passed through a hydrocarbon to convert a portion of the hydrocarbon into the corresponding organic hydroperoxide. Pure oxygen, air, or oxygen in combination with an inert gas such as nitrogen can be used.
[0093] In addition to the propylene oxide formation reaction, a secondary reaction occurs in the epoxidation stage by the catalytic decomposition of EBHP, in which acetophenone (ACP) is generated as a by-product. This side reaction leads to a lower selectivity of the hydroperoxide to propylene oxide. Typically, the selectivity of EBHP to ACP is in the range of 4 to 8%.
[0094] The epoxidation reaction can be carried out in the liquid phase in a solvent or diluent that is liquid at the reaction temperature and pressure and is substantially inert to the reactants and the products prepared therefrom. Typically, the same hydrocarbons used to prepare the organic hydroperoxide reactants can be used as solvents. For example, when utilizing ethylbenzene hydroperoxide, it is preferred to use ethylbenzene as the epoxidation solvent.
[0095] Optionally, ethylbenzene hydroperoxide is pretreated before the epoxidation reaction. The pretreatment comprises at least an alkali wash and a distillation step. Typical pretreatments of ethylbenzene hydroperoxide are described, for example, in US5883268A.
[0096] The epoxidation reaction can be carried out in the liquid phase in a solvent or diluent that is liquid at the reaction temperature and pressure and is substantially inert to the reactants and the products prepared therefrom. Typically, the same hydrocarbons used to prepare the organic hydroperoxide reactants can be used as solvents. For example, when utilizing ethylbenzene hydroperoxide, it is preferred to use ethylbenzene as the epoxidation solvent.
[0097] Suitable reaction temperatures vary from room temperature to 200° C., preferably from room temperature to 160° C., more preferably from 70° C. to 120° C. The reaction is preferably carried out at atmospheric pressure or above. Typical pressures vary from 1 atmosphere to 100 atmospheres, preferably from 40 atmospheres to 90 atmospheres.
[0098] The epoxidation may be carried out using any conventional reactor configuration known in the art for reacting an olefin with an organic hydroperoxide in the presence of an insoluble catalyst. Continuous as well as batch procedures may be used.
[0099] A preferred treatment for a continuous fixed bed process is a series of reactors loaded with catalysts. The EBHP solution can be divided into different reactors. For example, a preferred method of operating such an epoxidation facility using a heterogeneous catalyst is described in EP1047681A1.
[0100] In the context of the present invention, the terms "direct contacting" or "direct drying" or synonyms mean that no intermediate steps are carried out between the preceding step and the step mentioned (contacting, drying, ...).
[0101] Throughout the specification and claims, the word "comprises" and grammatical variations of the word are not intended to exclude other technical features, additives, components or steps. Additional objects, advantages and features of the present invention will become apparent to those skilled in the art after examining this specification, or may be learned by practicing the present invention. The following examples are provided by way of illustration, and they are not intended to limit the present invention.
[0102] Example
[0103] Embodiment 1:
[0104] Catalyst 1
[0105] 1800 liters of dilute sulfuric acid (16 wt%) were loaded in a fixed bed reactor. Then, 630 liters of water glass (viscosity of 500 mPa*s) were prilled into the dilute sulfuric acid. The water glass drops gelled immediately after contact with the acid and formed gel particles. The gel particles sank and formed a bed of gel particles in the reactor.
[0106] The sulfuric acid is circulated over the bed of gel particles and the ion exchange column in the reactor at a flow rate of 1600 to 2000 liters / hour. The acid is intended to remove trivalent, tetravalent and pentavalent metal ion impurities from the gel particles and transport them to the ion exchange column where they are adsorbed. The cycle is continued for about 75 to 80 minutes (depending on the desired purity).
[0107] The acid was then replaced with fresh dilute sulfuric acid. The acid was heated to 60° C. During the heating period, the acid was circulated again through the bed and the ion exchange column. The circulation was carried out for 80 minutes at a flow rate of 4000 liters per hour.
[0108] Then, the acid was drained and the gel particles were rinsed with deionized water at a flow rate of 8000 liters per hour for 60 minutes.
[0109] A solution of sulfuric acid (25 wt%) and titanium sulfate (3 to 4 wt%, aiming for a titanium content of the catalyst hydrogel precursor of 1.7 wt%) was circulated through the fixed bed gel particles in the reactor for 120 minutes.
[0110] The solution was replaced with deionized water and the gel particles were washed with deionized water at a flow rate of 10,000 liters per hour. 80 liters of ammonium acetate solution (50 wt%) were dosed into the deionized water stream, thereby adjusting the ammonium acetate concentration to about 7.5 wt% and raising the pH to 5.5 to 6.5. The solution was circulated through the fixed bed of gel particles in the reactor at 80 to 85° C. for 5 to 6 h.
[0111] Then, the ammonium acetate solution was replaced with deionized water, and washing was performed with deionized water at a flow rate of 8000 liters per hour for 60 minutes.
[0112] Finally, the water was rinsed off and the titanium-doped silica hydrogel was discharged from the reactor. The hydrogel synthesized in this way has a residual water content Xwa of about Xwa=55.5wt% and a Ti content of 1.69wt% (2.82wt% TiO2). The titanium content of the sample was determined by elemental analysis via optical emission spectroscopy with inductively coupled plasma (ICP-OES) after dissolving the following solids: 5ml of ultrapure water, 1.5ml of D-mannitol solution (1g of D-mannitol in 499g of ultrapure water) and 5ml of HF (40 to 50wt% aqueous solution) were added to 1g of the sample. Then, the resulting solution was heated to 120°C to remove the liquid. The remaining residue was successively dissolved in 1ml of HNO3 (65 to 70wt% aqueous solution) and 2ml of H2O2 under heat treatment at 120°C for 1h. The resulting liquid was diluted to 1 / 10 with ultrapure water before measurement.
[0113] The Ti content of the solid material mentioned in the present invention has been calculated based on the dry mass.
[0114] 500 g of the obtained hydrogel were then transferred to a drying cabinet, heated to 160° C. using a heating rate of 3° C. / min and kept at this temperature for 15 h in an air atmosphere. A residual water content Xwb of the obtained material of Xwb=3.2 wt% was found.
[0115] Thereafter, the dried material was calcined in a furnace at 800°C for 2 h under static conditions (a heating rate of 5°C / min was applied to reach the desired temperature) to obtain the following material characterized by 491 m 2 BET specific surface area A / g S,BET , average pore width D of 5.3 nm P,BJH and 0.8 cm 3 The pore volume V / g P,总 The BET specific surface area A S,BET , average pore width D P,BJH and the pore volume V P,总 is derived from the nitrogen physical adsorption isotherm measured on a Micromeritics ASAP2420 analyzer at 77 K. Prior to the measurement, each sample was degassed at 300 ° C. for 10 h in a vacuum of 40 to 50 mbar for the calcined material and at 110 ° C. for 10 h in a vacuum of 40 to 50 mbar for the hydrophobized material. The Brunnauer-Emmett-Teller (BET) method according to DIN 9277:2014 was used to calculate the specific surface area A S,BET . Average pore width D P,BJH and the total pore volume V P,总 is calculated by applying the Barrett, Joyner and Halenda (BJH) method using the desorption branch of the isotherm (see Journal of the American Chemical Society, 73: 373-380, 1951).
[0116] As shown by diffuse reflectance (DR)-UV / Vis, the measured reflectance is converted into Kubelka-Munk units (see Reflectance Spectroscopy, W. WM. Wendlandt, HG Hecht, Interscience Publishers / John Wiley NY, 1966; Reflectance Spectroscopy G. Kortüm, Springer Berlin, 1969; Interpreting Diffuse Reflectance and Transmittance: A Theoretical Introduction to Absorption Spectroscopy of Scattering Materials, DJ Dahm, KD Dahm, IMPublications Open LLP Chichester, 2007), the dried material also shows an intensity share of 90% below 275 nm and a band maximum centered at 233±5 nm. (PTFE, reflectance 99%) as a reference, the respective DR-UV / Vis spectra were collected on a Varian Cary 5000 spectrophotometer equipped with a diffuse reflectance (DR) sphere. Before each measurement, the samples were activated in a desiccator under vacuum for at least 5 h. The intensity component SI below 275 nm was b275 The intensity fraction below 275 nm is calculated by dividing the integral area (A) between 200 and 275 nm by eq. i,275 nm ) divided by the integrated area of the entire band between 200 and 375 nm (A i,总 ) is used to calculate. Band integration is performed to obtain area, just like chromatographic peak integration (see Gas Chromatography, IAFolis, Wiley & Sons Ltd, 1995).
[0117]
[0118] The calcination is followed by a hydrophobization step. For this purpose, 40 g of the calcined material are placed in a three-necked round-bottom flask, followed by the addition of 264 ml of toluene and 20 g of hexadimethylsilazane. The reaction mixture is stirred smoothly at 25° C. for 100 min. -1) for 1 hour, then heated to 110° C. and kept at this temperature for 3 hours. After cooling to 25° C., the solid was filtered off, partially dried in a nitrogen stream, and placed in a vacuum desiccator at a temperature not exceeding 110° C. overnight to remove the solvent.
[0119] The physicochemical characterization results of the catalysts are summarized in Table 1.
[0120] Evaluation of catalyst performance:
[0121] In order to evaluate the performance of the catalyst, a continuous fixed bed epoxidation of propylene and ethylbenzene hydroperoxide was carried out. Performance was tested in an isothermal fixed bed reactor (diameter = 10 mm, length = 1.75 m), and temperature was controlled by a jacket with hot oil. Catalyst loading is shown in Table 2, depending on the test. The catalyst was mixed with glass balls (1 mm) to improve temperature control, and both the top and bottom had glass balls (3 mm) with a larger diameter to protect the catalyst bed. The mixture was fed to the reactor from top to bottom.
[0122] The epoxidation of propylene was carried out with a solution of ethylbenzene hydroperoxide. A solution of 35wt% ethylbenzene hydroperoxide in ethylbenzene was used, and the ethylbenzene hydroperoxide was made by oxidation of ethylbenzene with air. The solution was pretreated according to the procedure described in US5883268. After pretreatment, the ethylbenzene hydroperoxide solution had an acid content lower than 500ppm, a water content lower than 5000ppm, and it also contained some methyl phenyl ketone and / or 1-phenyl-ethanol formed in the aforementioned oxidation. Typical ethylbenzene hydroperoxide feed contained 33 to 36wt% ethylbenzene hydroperoxide, 53 to 54wt% ethylbenzene, 2 to 4wt% 1-phenyl-ethanol and 3 to 5wt% methyl phenyl ketone. Propylene was added to the ethylbenzene hydroperoxide feed, and the mixture was fed into the fixed bed reactor.
[0123] Ethylbenzene hydroperoxide (EBHP) solution and propylene were continuously fed in the fixed bed reactor at 25°C. The amount of EBHP and propylene was adjusted with the amount of catalyst, keeping the ratio between EBHP, propylene and catalyst constant. See Table 2 for the exact amounts.
[0124] The reactor temperature was controlled at 100° C. and the reaction was carried out at a pressure of 60 bar. Once the reactor was in continuous operation at the set temperature, samples were taken every 24 h to analyze the outlet composition by GC and HPLC using Agilent 6850 and Agilent 1100 series chromatographs.
[0125] In Table 2, the following results are summarized for the epoxidation reactions using different catalysts: Conversion of ethylbenzene hydroperoxide XEBHP , the molar selectivity S for the secondary product acetophenone ACP ACP , and the pseudo-first order kinetic rate constant k' of heterogeneous reactions.
[0126] The conversion of ethylbenzene hydroperoxide is defined as the percentage of ethylbenzene hydroperoxide reacted. The selectivity to acetophenone ACP is defined as the molar percentage of ACP produced relative to EBHP reacted. The kinetic rate constant k' (L / gh) is defined by the following formula:
[0127]
[0128] where F A0 is the rate of EBHP at the reactor inlet (mol / h), C A0 is the concentration of EBHP at the reactor inlet (mol / L), w represents the weight of the catalyst (g), and X A is the conversion of EBHP as defined above. The calculations were performed taking into account the density of the reactant mixture at 100°C of 509 g / L.
[0129] The test results are summarized in Table 2.
[0130] Due to its unique properties, the catalyst prepared in this example showed a very high conversion rate X EBHP , selectivity and kinetic rate constant k', and also the selectivity S for the undesired product acetophenone ACP It is low.
[0131] Embodiment 2:
[0132] Catalyst 2 was prepared and characterized as described in Example 1, except for the drying step. The precursor (Xwa=55.5 wt%) synthesized as such was placed in a preheated drying oven at 160°C and kept at this temperature for 17 h. The dried material had a residual water content Xwb of Xwb=3.0 wt%.
[0133] The obtained materials were characterized with respect to their physicochemical properties and tested with respect to their catalytic properties as described in Example 1. The results are summarized in Tables 1 and 2.
[0134] Example 3: (Comparison - Ti content is too low)
[0135] Catalyst 3 was prepared and characterized as described in Example 1, except for the Ti content of the as-synthesized hydrogel (wherein the hydrogel had an Xwa of Xwa=58 wt%), the aging time and temperature, and the calcination step. The Ti content was 0.61 wt% (TiO2 1.02 wt%). The aged solution was circulated through the fixed bed gel particles in the reactor at 80 to 85°C for 5 to 6 h.
[0136] The dried material (with a residual water content Xwb of Xwb = 2.9 wt%) was calcined in a furnace at 600°C for 2 h under static conditions (a heating rate of 5°C / min was applied to reach the desired temperature).
[0137] The obtained materials were characterized with respect to their physicochemical properties and tested with respect to their catalytic properties as described in Example 1. The results are summarized in Tables 1 and 2.
[0138] Compared with catalysts 1 and 2, catalyst 3 has a lower Ti content, a lower proportion of pentahedrally coordinated Ti centers, and exhibits a lower conversion rate X. EBHP , selectivity and significantly lower kinetic rate constant k'. In addition, for catalyst 3, the selectivity S for undesirable products ACP Substantially higher.
[0139] Example 4: (Comparison - Ti content is too high)
[0140] Catalyst 4 was prepared and characterized as described in Example 1, with the difference being the Ti content of the hydrogel so synthesized (wherein the hydrogel had an Xwa of Xwa=57 wt% before drying), the aging time and temperature and the calcination step. The Ti content was 2.04 wt% (TiO2 3.41 wt%). The aging solution was circulated through the fixed bed gel particles in the reactor at 80 to 85°C for 5 to 6 h. The dried material, which exhibited a residual water content Xwb of Xwb=3.5 wt%, was calcined in a furnace at 600°C for 2 h under static conditions (a heating rate of 5°C / min was applied to reach the desired temperature).
[0141] The obtained materials were characterized with respect to their physicochemical properties and tested with respect to their catalytic properties as described in Example 1. The results are summarized in Tables 1 and 2.
[0142] Example 5: (non-hydrophobized)
[0143] Catalyst 5 (wherein the hydrogel synthesized as such has an Xwa of Xwa=55.5 wt%, and a Ti content of 1.69 wt% (2.82 wt% TiO2) and a residual water content Xwb after drying of Xwb=3.2 wt%) was prepared and characterized as described in Example 1, except that the calcined material was not hydrophobized. The materials tested were used in calcined form.
[0144] The obtained materials were characterized with respect to their physicochemical properties and tested with respect to their catalytic properties as described in Example 1. The results are summarized in Tables 1 and 2.
[0145] Example 6: (Comparative - Catalyst prepared by vapor deposition of TiCl4 on a silica support)
[0146] Catalyst 6 was prepared by vapor deposition of titanium tetrachloride (TiCl4) on a dry silica support. In a first pretreatment step, 120 g of silica (Aerolyst 3041, A S,BET =179m 2 / g,V P,总 =1.05cm 3 / g,D P,BJH =19 nm) was treated with aqueous HCl (w=4 mol / l) at 70°C for 60 minutes, followed by filtration and drying of the solid at 110°C for 4 h. The pretreated silica was then contacted with a gas stream containing TiCl4, obtained by heating TiCl4 to 200°C using a nitrogen stream N2 (60 l / h) as carrier gas. The impregnated silica (1.8 wt% titanium content) was then calcined at 590°C for 6 h, followed by steam treatment at 220°C for 3 h. Finally, the steam treated material was hydrophobized as described in Example 1 using 8 g of the steam treated material, 4 g of hexamethyldisilazane and 52 ml of toluene.
[0147] The obtained materials were characterized with respect to their physicochemical properties and tested with respect to their catalytic properties as described in Example 1. The results are summarized in Tables 1 and 2.
[0148] Example 7: (Aging step before titanium impregnation)
[0149] 1800 liters of dilute sulfuric acid (16 wt%) were loaded in a fixed bed reactor. Then, 630 liters of water glass (viscosity of 500 mPa*s) were granulated into the dilute sulfuric acid. The water glass drops gelled and formed gel particles immediately after contact with the acid. The gel particles sank and formed a bed of gel particles in the reactor.
[0150] The sulfuric acid is circulated through the gel particle bed and ion exchange column in the reactor at a flow rate of 1600 to 2000 liters per hour. The acid is intended to remove trivalent, tetravalent and pentavalent metal ion impurities from the gel particles and transport them to the ion exchange column where they are adsorbed. The cycle is continued for about 75 to 80 minutes.
[0151] The acid was then replaced with fresh dilute sulfuric acid. The acid was heated to 60° C. During the heating period, the acid was again circulated through the bed and the ion exchange column. The circulation was carried out for 80 minutes at a flow rate of 4000 liters / hour.
[0152] Then, the acid was drained and the gel particles were rinsed with deionized water at a flow rate of 8000 liters / hour for 60 minutes.
[0153] The solution was replaced with deionized water and the gel particles were washed with deionized water at a flow rate of 10,000 liters / hour. 80 liters of ammonium acetate solution (50 wt%) were dosed into the deionized water stream, thereby adjusting the ammonium acetate concentration to about 7.5 wt% and raising the pH to 5.5 to 6.5. The aged solution was circulated through the fixed bed of gel particles in the reactor at 80 to 85°C for 5 to 6 hours.
[0154] A solution of sulfuric acid (25 wt%) and titanium sulfate (3 to 4 wt%, aiming for 1.7 wt% of the titanium content of the catalyst hydrogel precursor) was circulated through the fixed bed gel particles in the reactor for 120 minutes.
[0155] The sulfuric acid solution was replaced with deionized water, and washed with deionized water at a flow rate of 8000 liters / hour for 60 minutes.
[0156] Finally, the water was rinsed off and the titanium-doped silica hydrogel was discharged from the reactor. The hydrogel synthesized in this way had a residual water content Xwa of about Xwa=57.5 wt% and a Ti content of 1.65 wt% (2.75 wt% TiO2). The titanium content of the sample was determined by elemental analysis via optical emission spectroscopy with inductively coupled plasma (ICP-OES) as described in Example 1. The Ti content of the solid material mentioned in the present invention has been calculated based on the dry mass.
[0157] 500 g of the obtained hydrogel were then transferred to a drying cabinet, heated to 160° C. using a heating rate of 3° C. / min and kept at this temperature for 15 h in an air atmosphere. A residual water content Xwb of the obtained material of Xwb=3.1 wt% was found.
[0158] Thereafter, the dried material was calcined in a furnace at 800° C. for 2 h under static conditions (a heating rate of 5° C. / min was applied to reach the desired temperature).
[0159] As described in Example 1, the intensity component SI below 275 nm is b275 The results are summarized in Table 1.
[0160] The calcination is followed by a hydrophobization step. For this purpose, 40 g of the calcined material are placed in a three-necked round-bottom flask, followed by the addition of 264 ml of toluene and 20 g of hexadimethylsilazane. The reaction mixture is stirred smoothly at 25° C. for 100 min. -1 ) for 1 hour, then heated to 110° C. and kept at this temperature for 3 hours. After cooling to 25° C., the solid is filtered off, partially dried in a nitrogen stream and placed in a vacuum desiccator at a temperature not exceeding 110° C. overnight in order to remove the solvent.
[0161] The obtained material was characterized with respect to its physicochemical properties as described in Example 1. The results are summarized in Table 1.
[0162] Evaluation of catalyst performance:
[0163] In order to evaluate the performance of the catalyst, a continuous fixed bed epoxidation of propylene and ethylbenzene hydroperoxide was carried out. Performance was tested in an isothermal fixed bed reactor (diameter = 10 mm, length = 1.75 m), and temperature was controlled by a jacket with hot oil. Catalyst loading is shown in Table 2, depending on the test. The catalyst was mixed with glass balls (1 mm) to improve temperature control, and both the top and bottom had glass balls (3 mm) with a larger diameter to protect the catalyst bed. The mixture was fed to the reactor from top to bottom.
[0164] The epoxidation of propylene was carried out with a solution of ethylbenzene hydroperoxide. A solution of 35wt% ethylbenzene hydroperoxide in ethylbenzene was used, and the ethylbenzene hydroperoxide was made by oxidation of ethylbenzene with air. The solution was pretreated according to the procedure described in US5883268. After pretreatment, the ethylbenzene hydroperoxide solution had an acid content lower than 500ppm, a water content lower than 5000ppm, and it also contained some methyl phenyl ketones and / or 1-phenyl-ethanol formed in the aforementioned oxidation. Typical ethylbenzene hydroperoxide feed contained 33 to 36wt% ethylbenzene hydroperoxide, 53 to 54wt% ethylbenzene, 2 to 4wt% 1-phenyl-ethanol and 3 to 5wt% methyl phenyl ketones. Propylene was added to the ethylbenzene hydroperoxide feed, and the mixture was fed into the fixed bed reactor.
[0165] Ethylbenzene hydroperoxide (EBHP) solution and propylene were continuously fed in the fixed bed reactor at 25°C. The amount of EBHP and propylene was adjusted with the amount of catalyst, keeping the ratio between EBHP, propylene and catalyst constant. See Table 2 for the exact amounts.
[0166] The reactor temperature was controlled at 100° C. and the reaction was carried out at a pressure of 60 bar. Once the reactor was continuously operated at the set temperature, samples were taken every 24 h to analyze the outlet composition by GC and HPLC using Agilent 6850 and Agilent 1100 series chromatographs.
[0167] In Table 2, the following results are summarized for the epoxidation reactions using different catalysts: Conversion of ethylbenzene hydroperoxide X EBHP , the molar selectivity S for the secondary product acetophenone ACP ACP , and the pseudo-first-order kinetic rate constant k' of heterogeneous reactions.
[0168] The conversion of ethylbenzene hydroperoxide is defined as the percentage of ethylbenzene hydroperoxide reacted. The selectivity to acetophenone ACP is defined as the molar percentage of ACP produced relative to EBHP reacted. The kinetic rate constant k' (L / gh) is defined by the following formula:
[0169]
[0170] where F A0 is the rate of EBHP at the reactor inlet (mol / h), C A0 is the concentration of EBHP at the reactor inlet (mol / L), w represents the weight of the catalyst (g), and X Ais the conversion of EBHP as defined above. The calculations were performed taking into account the density of the reactant mixture at 100°C of 509 g / L.
[0171] The test results are summarized in Table 2.
[0172] Example 8: (Comparison - Xwb is too low)
[0173] 1800 liters of dilute sulfuric acid (16 wt%) were loaded in a fixed bed reactor. Then, 630 liters of water glass (viscosity of 500 mPa*s) were granulated into the dilute sulfuric acid. The water glass drops gelled immediately after contact with the acid and formed gel particles. The gel particles sank and formed a bed of gel particles in the reactor.
[0174] The sulfuric acid is circulated through the gel particle bed and ion exchange column in the reactor at a flow rate of 1600 to 2000 liters / hour. The acid is intended to remove trivalent, tetravalent and pentavalent metal ion impurities from the gel particles and transport them to the ion exchange column where they are adsorbed. The cycle is continued for about 75 to 80 minutes.
[0175] The acid was then replaced with fresh dilute sulfuric acid. The acid was heated to 60° C. During the heating period, the acid was again circulated through the bed and the ion exchange column. The circulation was carried out for 80 minutes at a flow rate of 4000 liters / hour.
[0176] Then, the acid was drained and the gel particles were rinsed with deionized water at a flow rate of 8000 liters / hour for 60 minutes.
[0177] The solution was replaced with deionized water and the gel particles were washed with deionized water at a flow rate of 10,000 liters / hour. 80 liters of a solution of ammonium acetate (50 wt%) were dosed into the deionized water stream, thereby adjusting the ammonium acetate concentration to about 7.5 wt% and raising the pH to 5.5 to 6.5. The aged solution was circulated through the fixed bed of gel particles in the reactor at 80 to 85°C for 5 to 6 hours.
[0178] Then, the ammonium acetate solution was replaced with deionized water, and washing was performed with deionized water at a flow rate of 8000 liters / hour for 60 minutes.
[0179] Finally, the water was flushed away and the silica hydrogel was discharged from the reactor. The hydrogel synthesized in this way had a residual water content Xwa of about Xwa=58 wt%.
[0180] 500 g of the obtained hydrogel were then transferred to a drying cabinet, heated to 160° C. using a heating rate of 3° C. / min and kept at this temperature for 18 h in an air atmosphere. A residual water content Xwb of the obtained material of Xwb=0.16 wt% was found.
[0181] Then successively, the dried hydrogel was impregnated with a diluted titanium sulfate solution (15 m % titanium sulfate solution diluted in water to fill the pore volume of the hydrogel, aiming at a titanium content of the catalyst hydrogel precursor of 1.7 wt %).
[0182] The impregnated gel obtained was then transferred to a drying cabinet, heated to 160° C. at a heating rate of 3° C. / min, and kept at this temperature for 15 h in an air atmosphere.
[0183] Thereafter, the dried material was calcined in a furnace at 800° C. for 2 h under static conditions (a heating rate of 5° C. / min was applied to reach the desired temperature).
[0184] The obtained material was characterized with respect to its physicochemical properties as described in Example 1. The results are summarized in Table 1.
[0185] Evaluation of catalyst performance:
[0186] In order to evaluate the performance of the catalyst, a continuous fixed bed epoxidation of propylene and ethylbenzene hydroperoxide was carried out. Performance was tested in an isothermal fixed bed reactor (diameter = 10 mm, length = 1.75 m), and temperature was controlled by a jacket with hot oil. Catalyst loading is shown in Table 2, depending on the test. The catalyst was mixed with glass balls (1 mm) to improve temperature control, and both the top and bottom had glass balls (3 mm) with a larger diameter to protect the catalyst bed. The mixture was fed to the reactor from top to bottom.
[0187] The epoxidation of propylene was carried out with a solution of ethylbenzene hydroperoxide. A solution of 35wt% ethylbenzene hydroperoxide in ethylbenzene was used, and the ethylbenzene hydroperoxide was made by oxidation of ethylbenzene with air. The solution was pretreated according to the procedure described in US5883268. After pretreatment, the ethylbenzene hydroperoxide solution had an acid content lower than 500ppm, a water content lower than 5000ppm, and it also contained some methyl phenyl ketone and / or 1-phenyl-ethanol formed in the aforementioned oxidation. Typical ethylbenzene hydroperoxide feed contained 33 to 36wt% ethylbenzene hydroperoxide, 53 to 54wt% ethylbenzene, 2 to 4wt% 1-phenyl-ethanol and 3 to 5wt% methyl phenyl ketone. Propylene was added to the ethylbenzene hydroperoxide feed, and the mixture was fed into the fixed bed reactor.
[0188] Ethylbenzene hydroperoxide (EBHP) solution and propylene were continuously fed in the fixed bed reactor at 25°C. The amount of EBHP and propylene was adjusted with the amount of catalyst, keeping the ratio between EBHP, propylene and catalyst constant. See Table 2 for the exact amounts.
[0189] The reactor temperature was controlled at 100° C. and the reaction was carried out at a pressure of 60 bar. Once the reactor was continuously operated at the set temperature, samples were taken every 24 h to analyze the outlet composition by GC and HPLC using Agilent 6850 and Agilent 1100 series chromatographs.
[0190] In Table 2, the following results are summarized for the epoxidation reactions using different catalysts: Conversion of ethylbenzene hydroperoxide X EBHP , the molar selectivity S for the secondary product acetophenone ACP ACP and the pseudo-first-order kinetic rate constant k' of heterogeneous reactions.
[0191] The conversion of ethylbenzene hydroperoxide is defined as the percentage of ethylbenzene hydroperoxide reacted. The selectivity to acetophenone ACP is defined as the molar percentage of ACP produced relative to EBHP reacted. The kinetic rate constant k' (L / gh) is defined by the following formula:
[0192]
[0193] where F A0 is the rate of EBHP at the reactor inlet (mol / h), C A0 is the concentration of EBHP at the reactor inlet (mol / L), w represents the weight of the catalyst (g), and X A is the conversion of EBHP as defined above. The calculations were performed taking into account the density of the reactant mixture at 100°C of 509 g / L.
[0194] The test results are summarized in Table 2.
[0195] Example 9: (Comparison - Xwb is too high)
[0196] 1800 liters of dilute sulfuric acid (16 wt%) were loaded in a fixed bed reactor. Then, 630 liters of water glass (viscosity of 500 mPa*s) were granulated into the dilute sulfuric acid. The water glass drops gelled immediately after contact with the acid and formed gel particles. The gel particles sank and formed a bed of gel particles in the reactor.
[0197] The sulfuric acid was circulated through the gel particle bed and ion exchange column in the reactor at a flow rate of 1600 to 2000 liters / hour. The acid was intended to remove trivalent, tetravalent and pentavalent metal ion impurities from the gel particles and transport them to the ion exchange column where they were adsorbed. The cycle was continued for about 75 to 80 minutes.
[0198] The acid was then replaced with fresh dilute sulfuric acid. The acid was heated to 60° C. During the heating period, the acid was again circulated through the bed and the ion exchange column. The circulation was carried out for 80 minutes at a flow rate of 4000 liters / hour.
[0199] Then, the acid was drained and the gel particles were rinsed with deionized water at a flow rate of 8000 liters / hour for 60 minutes.
[0200] The solution was replaced with deionized water and the gel particles were washed with deionized water at a flow rate of 10,000 liters / hour. 80 liters of a solution of ammonium acetate (50 wt%) were dosed into the deionized water stream, thereby adjusting the ammonium acetate concentration to about 7.5 wt% and raising the pH to 5.5 to 6.5. The aged solution was circulated through the fixed bed of gel particles in the reactor at 80 to 85°C for 5 to 6 hours.
[0201] Then, the ammonium acetate solution was replaced with deionized water, and washing was performed with deionized water at a flow rate of 8000 liters / hour for 60 minutes.
[0202] Finally, the water was flushed away and the silica hydrogel was discharged from the reactor. The hydrogel synthesized in this way had a residual water content Xwa of about Xwa=58 wt%.
[0203] 500 g of the obtained hydrogel were then transferred to a drying cabinet, heated to 160° C. using a heating rate of 3° C. / min and kept at this temperature for 1 h in an air atmosphere. A residual water content Xwb of the obtained material of Xwb=25 wt% was found.
[0204] Then successively, the dried gel was impregnated with a diluted titanium sulfate solution (15 m % titanium sulfate solution diluted in water to fill the pore volume of the hydrogel, aiming at a titanium content of the catalyst hydrogel precursor of 1.7 wt %).
[0205] The impregnated gel obtained was then transferred to a drying oven, heated to 160° C. using a heating rate of 3° C. / min, and kept at this temperature for 15 h in an air atmosphere.
[0206] Thereafter, the dried material was calcined in a furnace at 800° C. for 2 h under static conditions (a heating rate of 5° C. / min was applied to reach the desired temperature).
[0207] The obtained material was characterized with respect to its physicochemical properties as described in Example 1. The results are summarized in Table 1.
[0208] Evaluation of catalyst performance:
[0209] In order to evaluate the performance of the catalyst, a continuous fixed bed epoxidation of propylene and ethylbenzene hydroperoxide was carried out. Performance was tested in an isothermal fixed bed reactor (diameter = 10 mm, length = 1.75 m), and temperature was controlled by a jacket with hot oil. Catalyst loading is shown in Table 2, depending on the test. The catalyst was mixed with glass balls (1 mm) to improve temperature control, and both the top and bottom had glass balls (3 mm) with a larger diameter to protect the catalyst bed. The mixture was fed to the reactor from top to bottom.
[0210] The epoxidation of propylene was carried out with a solution of ethylbenzene hydroperoxide. A solution of 35wt% ethylbenzene hydroperoxide in ethylbenzene was used, and the ethylbenzene hydroperoxide was made by oxidation of ethylbenzene with air. The solution was pretreated according to the procedure described in US5883268. After pretreatment, the ethylbenzene hydroperoxide solution had an acid content lower than 500ppm, a water content lower than 5000ppm, and it also contained some methyl phenyl ketone and / or 1-phenyl-ethanol formed in the aforementioned oxidation. Typical ethylbenzene hydroperoxide feed contained 33 to 36wt% ethylbenzene hydroperoxide, 53 to 54wt% ethylbenzene, 2 to 4wt% 1-phenyl-ethanol and 3 to 5wt% methyl phenyl ketone. Propylene was added to the ethylbenzene hydroperoxide feed, and the mixture was fed into the fixed bed reactor.
[0211] Ethylbenzene hydroperoxide (EBHP) solution and propylene were continuously fed in the fixed bed reactor at 25°C. The amount of EBHP and propylene was adjusted with the amount of catalyst, keeping the ratio between EBHP, propylene and catalyst constant. See Table 2 for the exact amounts.
[0212] The reactor temperature was controlled at 100° C. and the reaction was carried out at a pressure of 60 bar. Once the reactor was continuously operated at the set temperature, samples were taken every 24 h to analyze the outlet composition by GC and HPLC using Agilent 6850 and Agilent 1100 series chromatographs.
[0213] In Table 2, the following results are summarized for the epoxidation reactions using different catalysts: Conversion of ethylbenzene hydroperoxide X EBHP , the molar selectivity S for the secondary product acetophenone ACP ACPand the pseudo-first-order kinetic rate constant k' of heterogeneous reactions.
[0214] The conversion of ethylbenzene hydroperoxide is defined as the percentage of ethylbenzene hydroperoxide reacted. The selectivity to acetophenone ACP is defined as the molar percentage of ACP produced relative to EBHP reacted. The kinetic rate constant k' (L / gh) is defined by the following formula:
[0215]
[0216] where F A0 is the rate of EBHP at the reactor inlet (mol / h), C A0 is the concentration of EBHP at the reactor inlet (mol / L), w represents the weight of the catalyst (g), and X A is the conversion of EBHP as defined above. The calculations were performed taking into account the density of the reactant mixture at 100°C of 509 g / L.
[0217] The test results are summarized in Table 2.
[0218] Table 1: Physicochemical properties of the catalysts obtained as described in Examples 1 to 9, namely BET specific surface area A S,BET , average pore width D P,BJH , total pore volume V P,总 , such as the intensity fraction SI below 275nm derived from DR-UV / Vis b275 and band maximum and Ti content
[0219]
[0220] 1 BET specific surface area A S,BET / 2 Average pore width D P,BJH / 3 Total pore volume V P,总 Derived from nitrogen physical adsorption at 77K; 4 5 The measured reflectance was converted to Kubelka-Munk units as derived from DR-UV / Vis; 6 Determined by elemental analysis via IC-OES.The experimental procedure is described in Example 1.
[0221] Table 2: Catalytic performance of the tested catalysts, namely ethylbenzene hydroperoxide X EBHP , selectivity for acetophenone ACP and kinetic rate constant k' values. Test conditions are given in the footnotes.
[0222]
[0223] *80 g / h of ethylbenzene hydroperoxide solution / 256 g / h of propylene @ 25°C / the reactor was charged with 20 g of catalyst.
[0224] **40 g / h ethylbenzene hydroperoxide solution / 128 g / h propylene @ 25°C / reactor loaded with 10 g catalyst
[0225] ndUndetermined
[0226] As can be seen from Table 2 above, compared to the comparative catalyst, the catalyst according to the present invention shows a higher conversion rate X of EBHP as measured at different operating time (TOS). EBHP and a higher kinetic rate constant k'. It is worth mentioning that the selectivity for acetophenone S ACP is a critical parameter because the percentage of ACP constitutes process loss. EBHP At the same time as the kinetic rate constant k′, the catalyst according to the invention exhibits lower values of selectivity to the secondary product ACP, thus significantly exceeding the performance of the comparative catalyst.
Claims
1. A method for producing a catalyst comprising amorphous titanium-doped silica comprising a pentahedrally coordinated titanium species, the method comprising the following steps: a. a sol-gel synthesis of a catalyst hydrogel precursor, the sol-gel synthesis comprising the following steps: i. adding water glass exhibiting a viscosity in the range of 400 to 600 mPa*s to the acid, thereby producing a silica gel exhibiting a residual water content Xwa in the range of Xw1 to Xw2, ii. removing impurities from the silica gel by washing the silica gel with an acidic aqueous solution, thereby producing purified silica gel, iii. Forming a catalyst hydrogel precursor via alternative a: doping the purified silica gel by contacting the purified silica gel with an acidic aqueous solution of a titanium salt, thereby producing titanium-doped silica gel, and aging the titanium-doped silica gel by suspending it in an aging solution at a temperature in the range of 60° C. to 90° C. for a time span in the range of 4 h to 6 h, wherein the liquid portion of the suspension thus formed exhibits a pH value in the range of 5.5 to 7.5, thereby producing a catalyst hydrogel precursor exhibiting a titanium content Xt in the range of Xt1 to Xt2, or, The catalyst hydrogel precursor is formed via alternative b as follows: aging the purified silica gel by suspending the purified silica gel in an aging solution at a temperature in the range of 60° C. to 90° C. for a time span in the range of 4 h to 6 h, wherein the liquid portion of the suspension thus formed exhibits a pH value in the range of 5.5 to 7.5, thereby producing an aged purified silica gel, and doping the aged purified silica gel by contacting the aged purified silica gel with an acidic aqueous solution of a titanium salt, thereby producing a catalyst hydrogel precursor exhibiting a titanium content Xt in the range of Xt1 to Xt2, d. drying the catalyst hydrogel precursor until the residual water content Xwb of the dried catalyst hydrogel precursor is in the range of Xw3 to Xw4, e. calcining the dried catalyst hydrogel precursor, in, Xw1=40wt%, Xw2=60wt%, Xt1=0.85wt%, Xt2=1.9wt%, Xw3=1wt%, Xw4=7wt%, And among them, The residual water content Xwa and Xwb of the sample is determined as the weight loss exhibited by a 100 g-aliquot after drying in a drying cabinet at 200° C. for four hours under atmospheric conditions, And among them, The titanium content Xt of the sample was determined by elemental analysis via optical emission spectroscopy with inductively coupled plasma (ICP-OES) after: dissolving the sample by adding 5 ml of ultrapure water, 1.5 ml of a 0.2 wt % D-mannitol aqueous solution and 5 ml of a 40 wt % to 50 wt % HF aqueous solution to 1 g of the sample; subsequently removing the liquid component by heating to 120° C.; and successively, dissolving the remaining residue in 1 ml of a 65 wt % to 70 wt % HNO 3 aqueous solution and 2 ml of H 2 O 2 under heat treatment at 120° C. for 1 h; and diluting the resulting liquid 10 times with ultrapure water before measurement, And among them, The Ti content of the solid material is calculated on a dry mass basis and corresponds to the content of elemental titanium.
2. The method according to claim 1, further comprising step d: f. The calcined catalyst hydrogel precursor is hydrophobized with a hydrophobizing agent in a liquid phase.
3. The method according to any one of claims 1 to 2, wherein Xt is selected in the range of Xt1 = 1 wt% to Xt2 = 1.9 wt%, preferably in the range of Xt1 = 1.4 wt% to Xt2 = 1.8 wt%.
4. The method according to any one of claims 1 to 3, wherein the catalyst hydrogel precursor exhibits a residual water content Xwa in the range of Xw1=45wt% to Xw2=60wt%, preferably in the range of Xw1=47wt% to Xw2=60wt%, more preferably in the range of Xw1=52wt% to Xw2=57wt%.
5. Catalyst for use in the conversion of propylene into propylene oxide in a propylene oxide / styrene monomer process, said catalyst being obtainable by a process according to any one of claims 1 to 4.
6. The catalyst according to claim 5, wherein the catalyst exhibits a 2 The BET specific surface area A in the range of s,BET , preferably between 400 and 550 m 2 The BET specific surface area A in the range of s,BET .
7. The catalyst according to any one of claims 5 to 6, which exhibits an average pore width D in the range of 4 to 8 nm. P,BJH , preferably with an average pore width D in the range of 4 to 5 nm P,BJH , The average pore width D P,BJH is derived from nitrogen physisorption isotherms as measured on a Micromeritics ASAP 2420 analyzer at 77 K, wherein prior to the measurement each sample was degassed at 300 °C for 10 h in a vacuum of 40 to 50 mbar for the calcined material and at 110 °C for 10 h in a vacuum of 40 to 50 mbar for the hydrophobized material, and the average pore width D P,BJH is calculated by applying the method of Barrett, Joyner and Halenda (BJH) using the desorption branch of the isotherm as described in Journal of the American Chemical Society, 73:373-380, 1951.
8. The catalyst according to any one of claims 5 to 7, which exhibits a 3 The pore volume V in the range of P,总 , preferably between 0.7 and 0.9 cm 3 The pore volume V in the range of P,总 , The pore volume V P,总 is derived from nitrogen physisorption isotherms as measured on a Micromeritics ASAP 2420 analyzer at 77 K, wherein prior to the measurement each sample was degassed at 300° C. for 10 h in a vacuum of 40 to 50 mbar for the calcined material and at 110° C. for 10 h in a vacuum of 40 to 50 mbar for the hydrophobized material, and the pore volume V P,总 is calculated by applying the Barrett, Joyner and Halenda (BJH) method using the desorption branch of the isotherm as described in Journal of the American Chemical Society, 73:373-380, 1951.
9. The catalyst according to any one of claims 5 to 8, which exhibits the following: a. Titanium content in the range of 1.6 to 1.8 wt%, b.400 to 450m 2 BET specific surface area A / g s,BET , e. Average pore width D of 4.5 to 5 nm P,BJH , f.0.7 to 0.8 cm 3 The pore volume V / g P,总 , The titanium content Xt of the sample was determined by elemental analysis via optical emission spectroscopy with inductively coupled plasma (ICP-OES) after: dissolving the sample by adding 5 ml of ultrapure water, 1.5 ml of a 0.2 wt % D-mannitol aqueous solution and 5 ml of a 40 wt % to 50 wt % HF aqueous solution to 1 g of the sample; subsequently removing the liquid component by heating to 120° C.; and successively, dissolving the remaining residue in 1 ml of a 65 wt % to 70 wt % HNO 3 aqueous solution and 2 ml of H 2 O 2 under heat treatment at 120° C. for 1 h; and diluting the resulting liquid 10 times with ultrapure water before measurement, And among them, The Ti content of solid materials is calculated on a dry mass basis and corresponds to the content of elemental titanium, The average pore width D P,BJH is derived from nitrogen physisorption isotherms as measured on a Micromeritics ASAP 2420 analyzer at 77 K, wherein prior to the measurement each sample was degassed at 300 °C for 10 h in a vacuum of 40 to 50 mbar for the calcined material and at 110 °C for 10 h in a vacuum of 40 to 50 mbar for the hydrophobized material, and the average pore width D P,BJH is calculated by applying the method of Barrett, Joyner and Halenda (BJH) using the desorption branch of the isotherm, as described in Journal of the American Chemical Society, 73:373–380, 1951, The pore volume V P,总 is derived from nitrogen physisorption isotherms as measured on a Micromeritics ASAP 2420 analyzer at 77 K, wherein prior to the measurement each sample was degassed in vacuum at 300° C. for 10 h for the calcined material and at 110° C. for 10 h for the hydrophobized material, and the pore volume V P,总 is calculated by applying the method of Barrett, Joyner and Halenda (BJH) using the desorption branch of the isotherm as described in Journal of the American Chemical Society, 73:373-380, 1951.
10. A process for the preparation of propylene oxide comprising the reaction of propylene with ethylbenzene hydroperoxide in the presence of a catalyst according to claims 5 to 9.
Citation Information
Patent Citations
Epoxidation process using serially connected cascade of fixed bed reactors
EP1047681A1
Process for preparing an epoxidation catalyst and process for preparing epoxides
EP1572362A1
Relating to epoxidation catalysts
US20150182959A1
Method for fabricating a titanium-containing silicon oxide material with high thermal stability and applications of the same
US20180147560A1
Olefin epoxidation
US4367342A